2018
DOI: 10.1111/bjso.12242
|View full text |Cite
|
Sign up to set email alerts
|

How trust and emotions influence policy acceptance: The case of the Irish water charges

Abstract: The introduction of new policies can evoke strong emotional reactions by the public. Yet, social-psychological research has paid little attention to affective determinants of individual-level policy acceptance. Building on recent theoretical and empirical advances around emotions and decision-making, we evaluate how people's trust and integral emotions function as important antecedents of cognitive evaluations, and subsequent acceptance of policies. We test our hypotheses within a sample of Irish citizens (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 80 publications
2
26
0
Order By: Relevance
“…The latter should also be seen in the context of a recent debate about water taxes in Ireland whereby the government, in 2015, introduced water charges for all Irish citizens. As of mid‐2016, these taxes were abolished due to public protests and refusal to pay (Rodriguez‐Sanchez, Schuitema, Claudy, & Sancho‐Esper, ). Hence, the abolishment of the water charges meant that private well owners were once again the only people paying for drinking water in Ireland, which strengthened feelings of distrust and unfairness when discussing government intervention.…”
Section: Resultsmentioning
confidence: 99%
“…The latter should also be seen in the context of a recent debate about water taxes in Ireland whereby the government, in 2015, introduced water charges for all Irish citizens. As of mid‐2016, these taxes were abolished due to public protests and refusal to pay (Rodriguez‐Sanchez, Schuitema, Claudy, & Sancho‐Esper, ). Hence, the abolishment of the water charges meant that private well owners were once again the only people paying for drinking water in Ireland, which strengthened feelings of distrust and unfairness when discussing government intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Research in other areas found that trusting policies can also be achieved through people’s emotional responses. The authors believe that irrational actions based on emotional judgments are more likely to be due to people’s lack of knowledge or experience about new, unknown, and ambiguous events [ 43 ]. In the case of COVID-19, many researchers have found that government trust affects people’s risk perceptions, protective behaviors, and behavioral intentions [ 44 , 45 ].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The literature suggests that emotions and positive affect may drive proenvironmental behaviors (e.g., Vining and Ebreo, 2002;Bissing-Olson et al, 2013) and the desire to engage in pro-environmental action (e.g., Carrus et al, 2008). However, instead of considering general emotions and positive affect, studies have predominantly analyzed the influence of individual positive and negative emotions related to specific topics such as introducing a new water charge (Rodriguez-Sanchez et al, 2018) or engaging in different pro-environmental behaviors (Bissing-Olson et al, 2016;Carrus et al, 2008). This study focuses on happiness.…”
Section: For Completeness the Possible Association Between Personal mentioning
confidence: 99%